Adherence to the international thromboprophylaxis guidelines in patients undergoing major orthopaedic surgery in Colombia: Results of the DEIMOS registry - Bonilla, Guillermo; Llinás, Adolfo; Sánchez, Alfredo; Monsalve, Sergio; Matson, Gustavo; Valenzuela, Etna Liliana (Revista Colombiana de Ortopedia y Traumatología, 2020)
Background: Patients who undergo major orthopaedic surgery have an elevated risk of venous thromboembolism (VTE). International guidelines recommendations for VTE prevention have shown to be effective in reducing the frequency of thromboembolic events, but compliance to these recommendations is still low. The purpose of the present study is to report the adherence to the American College of Chest Physicians (ACCP) guidelines 2008 in Colombia. Material and methods: A report is presented on the Colombian results for the DEIMOS registry. This is a multinational, multicentre, observational, longitudinal study. Twenty orthopaedic wards were asked to include consecutive patients who were admitted for major orthopaedic surgery. Patient demographics, surgical information, type of anaesthesia and VTE prophylaxis were prospectively recorded, and the use of VTE prevention methods was assessed during the following visits. Adherence to the 2008 ACCP guidelines was then determined. Results: A total of 244 patients were included in Colombia, and 240 of them had a complete follow-up. The analysis included 108 total knee arthroplasties, 77 hip replacements and 59 hip fracture surgeries. Adherence to 2008 ACCP guidelines for in-hospital prophylaxis was 80.5% (95% CI; 71.7-89.4) for hip arthroplasty, 82.4% (95% CI; 75.2-89.6) for knee arthroplasty, and 94.9% CI; 89.3-100.0) for hip fracture surgeries. Adherence for extended prophylaxis was 75.3% (95% CI; 65.7-85.0) for hip arthroplasties, 73.1% (95% CI; 64.8-81.5) for knee arthroplasties, and 93.2% (95% CI; 86.8-99.6) for hip fracture surgery. Discussion: The DEIMOS registry reports good compliance to VTE prophylaxis guidelines after hip fracture surgery in Colombia. However, adherence to extended prophylaxis guidelines is still low after total hip and knee arthroplasties. Efforts should be made to improve the protection of these patients after hospital discharge.